How Ethical Leadership Shapes Employees’ Readiness to Change: The Mediating Role of an Organizational Culture of Effectiveness - Metwally, Dina; Ruiz-Palomino, Pablo; Metwally, Mohamed; Gartzia, Leire (Frontiers in Psychology, 2019)
Today’s organizations are operating in a highly competitive and changing environment that pushes them to continuously adapt their organizational structures to such environment. However, the success of change initiatives may face a barrier in the response of employees, especially when they lack readiness to change. While leadership can shape the culture of an organization and a culture of effectiveness can help increase employees’ readiness to change, ethical leaders, who serve as a guide and offer support, can also make a difference by reducing uncertainty. Yet existing research on the role of ethical leadership in the enhancement of the employees’ readiness to change is practically non-existent. Far less is the research that analyses the mechanisms that ethical leadership can use to foster employees’ readiness to change. This study aims to investigate whether the ethical leadership of middle–lower echelons influences on employees’ readiness to change positively (H1) and if this relationship is mediated through shaping an organizational culture of effectiveness (H2). Using data from 270 direct reports of middle–lower managers in public foreign trade Egyptian companies, the findings reveal that ethical leadership enhances employees’ readiness to change and that this impact is partially mediated by an organizational culture of effectiveness. Thus, with these findings, new light is shed on the positive role of ethical leadership and the mechanisms it uses to enhance employees’ readiness to change.